2018
DOI: 10.1097/01.nep.0000000000000291
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety and Academic Procrastination Among Prelicensure Nursing Students

Abstract: Test anxiety may cause nursing students to cope poorly with academic demands, affecting academic performance and attrition and leading to possible failure on the National Council Licensure Examination for Registered Nurses (NCLEX-RN®). Test-anxious nursing students may engage academic procrastination as a coping mechanism. The Test Anxiety Inventory and the Procrastination Assessment Scale for Students were administered to 202 prelicensure nursing students from diploma, associate, and baccalaureate nursing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 2 publications
2
19
0
3
Order By: Relevance
“…Research indicated that there was a significant inverse moderate correlation between EI and academic procrastination in a medical student (Mappakaya et al, ). Nursing students with lower EI and who are prone to experiencing negative emotions and academic procrastination also tend to experience considerable stress and anxiety in their learning tasks, and adverse physiological reactions (Custer, ). Those with higher EI may be more able to identify a specific emotion in stressful situations, spend less time focusing on their negative emotional reactions, quickly gain and maintain a more positive state of mind and employ cognitive resources that enable them to engage in less academic procrastination (Ruizaranda & Extremera, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research indicated that there was a significant inverse moderate correlation between EI and academic procrastination in a medical student (Mappakaya et al, ). Nursing students with lower EI and who are prone to experiencing negative emotions and academic procrastination also tend to experience considerable stress and anxiety in their learning tasks, and adverse physiological reactions (Custer, ). Those with higher EI may be more able to identify a specific emotion in stressful situations, spend less time focusing on their negative emotional reactions, quickly gain and maintain a more positive state of mind and employ cognitive resources that enable them to engage in less academic procrastination (Ruizaranda & Extremera, ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common academic related problems that lead to profound anxiety among college students are exams and the anticipation of having to take the exam. Test anxiety may lead to poor performance not because the student did not prepare well for the exam but for some reasons, the overwhelming feeling of fear of failure affects their concentration and focus thus affecting their performance in the exam (Custer, 2018). In this aspect, the school nurse has a responsibility to provide intervention and assist faculty members and other employees to help the students cope with it.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, researchers demonstrated the use of experienced workforce and structural problems as the main challenges faced by the managers. Since the responsible and efficient workforce is considered the most important assets for an organisation [28], [29], identifying the influential employees can improve their efficiency and realise their goals in line with organisational objectives. The next important and effective factor in managing the managers is disrupting organisational correlations.…”
Section: Discussionmentioning
confidence: 99%